2010
DOI: 10.1016/j.chom.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Formyl Peptide Receptor 2 Senses Highly Pathogenic Staphylococcus aureus

Abstract: SUMMARY Virulence of the emerging Community-Associated Methicillin-Resistant Staphylococcus aureus (CA-MRSA) and other highly pathogenic S. aureus depends on the recently discovered phenol-soluble modulin (PSM) peptide toxins, which combine the capacities to attract and lyse neutrophils. The molecular basis of PSM-stimulated neutrophil recruitment has remained unknown. We demonstrate that the human formyl peptide receptor 2 (FPR2/ALX), which has previously been implicated in control of endogenous inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
364
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(387 citation statements)
references
References 42 publications
21
364
1
1
Order By: Relevance
“…High-affinity formyl peptides for FPR1 have been found in both Escherichia coli (fMLF) and S. aureus (fMIFL), and neither of these peptides interacts with FPR2 (41,42); accordingly, we found the neutrophil response to these agonists to be insensitive to PBP10. We also found that PBP10 completely abolished the neutrophil response induced by two newly described formyl peptides derived from S. aureus exerting high binding affinity for FPR2 (12). Apparently, the presence of a formyl group does not play a significant role in mediating receptor specificity between FPR1 and FPR2 (43).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…High-affinity formyl peptides for FPR1 have been found in both Escherichia coli (fMLF) and S. aureus (fMIFL), and neither of these peptides interacts with FPR2 (41,42); accordingly, we found the neutrophil response to these agonists to be insensitive to PBP10. We also found that PBP10 completely abolished the neutrophil response induced by two newly described formyl peptides derived from S. aureus exerting high binding affinity for FPR2 (12). Apparently, the presence of a formyl group does not play a significant role in mediating receptor specificity between FPR1 and FPR2 (43).…”
Section: Discussionmentioning
confidence: 77%
“…flammatory mediators (9,12,29,32,33). Although the two receptors share large sequence similarities and induce almost identical cellular responses, there is one fundamental difference in their downstream signaling; that is, the FPR2 signaling is PBP10 sensitive, whereas the FPR1 signaling is PBP10 insensitive (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009;Cheung, Rigby et al 2010). This response is mediated by activation of the 29 human formyl peptide receptor 2 (FPR2) (Kretschmer, Gleske et al 2010). Thirdly,…”
mentioning
confidence: 99%
“…Excessive phenol soluble modulin (PSMs) production of CA-MRSA has been associated with higher virulence 4,5 . Human neutrophils can recognize these PSMs via FPR2 which lead to activation of this G-protein coupled receptor 6 . One of the earliest events is the mobilization of intracellular stores of calcium (Ca 2+ ).…”
Section: Introductionmentioning
confidence: 99%